Experiences of primary care professionals providing healthcare to recently arrived migrants: a qualitative study. Issue 9 (22nd September 2016) - Lindenmeyer, Antje; Redwood, Sabi; Griffith, Laura; Teladia, Zaheera; Phillimore, Jenny
Abstract : Objectives: The main objectives of the study were to explore the experiences of primary care professionals providing care to recent migrants in a superdiverse city and to elicit barriers and facilitators to meeting migrants' care needs. This paper focuses on a strong emergent theme: participants' descriptions and understandings of creating a fit between patients and practices. Design: An exploratory, qualitative study based on the thematic analysis of semistructured interviews. Setting and participants: A purposive sample of 10 practices. We interviewed 6 general practitioners, 5 nurses and 6 administrative staff; those based at the same practice opted to be interviewed together. 10 interviewees were from an ethnic minority background; some discussed their own experiences of migration. Results: Creating a fit between patients and practice was complex and could be problematic. Some participants defined this in a positive way (reaching out, creating rapport) while others also focused on ways in which patients did not fit in, for example, different expectations or lack of medical records. A small but vocal minority put the responsibility to fit in on to migrant patients. Some participants believed that practice staff and patients sharing a language could contribute to achieving a fit but others outlined the disadvantages of over-reliance on language concordance. A clearly articulated, team-based strategy to create bridges between practice and patients was often seen as preferable. Conclusions: Although participants agreed that a fit between patients and practice was desirable, some aimed to adapt to the needs of recently arrived migrants, while others thought that it was the responsibility of migrants to adapt to practice needs; a few viewed migrant patients as a burden to the system. Practices wishing to improve fit might consider developing strategies such as introducing link workers and other 'bridging' people; however, they could also aim to foster a general stance of openness to diversity.